Modelling the effect of dammar additions on the mass loss response of soy wax/beeswax/dammar blends via response surface methodology - Syed Shaharuddin, Sharifah Imihezri; Abd Aziz, Nor Busyra; Bacho, Nursyawalina; Muhamad Khairussaleh, Nor Khairusshima; Tumian, Afidalina; Zakaria, Irnie Azlin (IOP Publishing Ltd, 2021)
The wax used in the batik industry plays a significant role as its composition dictates the ease of wax rendering, dye layering, and wax removal process. This study aims to evaluate the effect of dammar additions on soy wax/beeswax blends based on the mass loss (%) of the wax-covered cotton fabric in 100C water. Central composite design (CCD), a subset of response surface methodology (RSM) was used to develop a response model (Y: mass loss %) for three independent variables (X1:beeswax, X2:soy wax, X3:dammar). The final quadratic response model obtained (F value =5.43, lack of fit F value = 4.70, adequate precision = 7.65) was proposed in this study. ANOVA analysis showed that the standard error of design was relatively small, ranging between 0.43 to 1.18 for the design space. It was deduced from the response model, that increasing the dammar content in the soy wax/beeswax blends increases the mass loss (%), possibly due to the compositional inhomogeneity of the blends. The result of this study shows great potentials in formulating new soy wax-based compositions that produce varying degrees of ease of wax removal for the batik industry.